Dynamic Compression Tests – Current Achievements and Future Development - W. MOĆKO; Z. L. KOWALEWSKI (Engineering Transactions, 2014)
In this paper a modified arrangement of the DICT technique was introduced. Miniatur- ization of bar and use of shadow principle to make a measurement of displacement allow to obtain strain rate up to 2.2×105 s−1. Commonly used methods of elimination of friction, iner- tia and adiabatic heating were presented. In order to estimate the rate sensitivity of a material (tantalum), quasi-static and SPHB tests were performed at room temperature within the rate spectrum ranging from 5×10−4 s−1 to 103 s−1. The final true stress versus true strain curves at different strain rates were corrected to a constant temperature and zero friction.